Environment friendly pesticide formulation by adding certain adjuvants and their biological performance against Sitophilus oryzae (L.) - Saad A. S. A.; Ahmed M. A. Kordy; Marwa I. Mackled; Amira E. Ahmed; Shimaa S. Abd El-Naby (Scientific Reports)
Abstract Formulation and adjuvant technologies can facilitate the use of insecticides that have higher biological efficiency application features. Safety, physicochemical properties by increasing consumer demand for safe food and enhancing operator safety. The aim of this current work was to develop a green efficient, and stable pesticide formulation. Therefore, certain nano emulsions with and without Adjuvants Calcium Alkyl Benzene Sulphonate (Atlox 4838B), and non-ionic surfactant based on trisiloxane ethoxylate (ARGAL), were testing against Sitophilus oryzae (Coleoptera: Curculionidae). Certain analytical techniques were used for determining the characterization of the nano emulsions (Sesame, Clove, and Cinnamon). Results showed that all formulations were penal, achieving nanometric size for all compounds. Scanning Electron Microscopy (SEM) micrographs revealed spherical or quasi-spherical morphologies for the tested nanoemulsion formulation nanodroplets. Furthermore, dynamic light scattering (DLS) showed that the particle size of the formulation with the adjuvants showed a slight increase in the droplet size compared to the formulations without adjuvants. In comparison to the tested nanoemulsions with adjuvants, the viscosity of the nanoemulsions without adjuvants was lower. All studied formulations, both with and without adjuvant, showed an acidic to slightly acidic pH, except for sesame (NE) with AtloxTM 4838B, which showed a neutral pH, and they were kinetically stable with no phase separation, creaming, or crystallization. Furthermore, supporting the stability of these nanoemulsion particles was the absence of a separation phase following centrifugation, freeze–thaw cycles, and heating–cooling cycles. Findings proved that ARGAL and Atlox 4838B adjuvant stabilized NE by increasing Brownian motion, weakening the attractive forces with smaller droplets, increasing the value of zeta potential and polydispersive index (< 0.6), and decreasing surface tension. The bioassay technique using film residue to estimate LC50 values on S. oryzae adults indicate that Clove, Sesame, and Cinnamon nano emulsions with Atolx adjuvants were the most effective against S. oryzae adults under laboratory conditions, where the LC50 Values are 0.022, 0.032 and 0.035 µL/cm2 respectively after 27 h, or exposure time. Clove, Cinnamon, and Sesame nanoemulsion (NE) with 0.01% (w/w) adjuvant exhibited remarkable insecticidal activity against S. oryzae L., of 100, 100 and 97.5% respectively by in vitro assay.